Role of Immediate Release and Delayed Release Omeprazole in Patients with Gastro Esophageal Reflux Disease (Faridpur Medical College Journal, 2017)
Proton pump inhibitors are widely used for Gastro Esophageal Reflux Disease (GERD) treatment. This prospective double blind randomized cross over study was carried out in the Department of Gastroenterology, BSMMU from June 2007 to May 2008 to assess the efficacy of Immediate-release omeprazole (IR-OMEP) & Delayed-release Omeprazole (DR-OMEP) in relieving symptoms & healing of oesophagitis in GERD. All patients who fulfilled the inclusion criteria underwent upper gastrointestinal (UGI) endoscopy to be lebelled as nonerosive and erosive GERD. Among total 69 patients, 43 (62.3 %) had nonerosive and 26 (37.7 %) had erosive GERD. Patients were divided into group A (35) and group B (34) who received group A drugs (20 mg IR-OMEP bd) and group B drugs (20 mg DROMEP bd) from day 1-14 respectively. Then drugs were crossed over (group A: 20mg DR-OMEP bd; group B: 20 mg IR-OMEP bd) from day 15-28. Improvement of heartburn, regurgitation in each group were assessed in every week, during drug cross over and at the end and then compared between two groups. There was no significant difference in relieving heartburn and regurgitation between IR-OMEP and DR-OMEP either in erosive or nonerosive GERD (P>0.50). Patients with erosive GERD underwent UGI endoscopy at the end of treatment to see healing of esophagitis. Study showed significant healing of oesophagitis in group A after 4 weeks than group B (14%) (P